Corneal Repair and Regeneration: Current Concepts and Future Directions - Mobaraki, Mohammadmahdi; Abbasi, Reza; Omidian Vandchali, Sajjad; Ghaffari, Maryam; Moztarzadeh, Fathollah; Mozafari, Masoud (Frontiers in Bioengineering and Biotechnology, 2019)
Cornea is a unique tissue which is the most powerful focusing element of the eye and known as a window to the eye.‏ Infectious or noninfectious diseases might cause severe visual impairments that need‏ medical interventions to restore patients' vision. The most prominent characteristics of the cornea are its mechanical strength and transparency which are indeed the most important criteria considerations in order to reconstruct the injured cornea. Corneal strength comes from about 200 collagen lamellae which criss-cross the cornea in different directions and comprise nearly 90% of the thickness of the cornea. Regarding corneal transparency, the specific characteristics of the cornea include its immune and angiogenic privilege besides its limbus zone. On the other hand, angiogenic privilege involves several active cascades in which anti-angiogenic factors are produced to compensate for the enhanced production of proangiogenic factors after wound healing. Limbus of the cornea forms a border between the corneal and conjunctival epithelium and its limbal stem cells (LSCs) are essential in maintenance and repair of the adult cornea through supporting of corneal epithelial tissue repair and regeneration. As a result, the main factors which threaten the corneal clarity are inflammatory reactions, neovascularization, and limbal deficiency. In fact, influxing of inflammatory cells causes scar formation and destruction of limbs zone. Current studies about wound healing treatment focus on a corneal characteristic like an immune response, angiogenesis, and cell signaling. In this review, studied topics related to the wound healing and new approaches in cornea regeneration which are mostly related to the criteria mentioned above will be discussed.